2002
DOI: 10.1046/j.1523-5394.2002.101009.x
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Change Related to Smoking Behavior Among Cancer Patients

Abstract: These findings suggest that behavioral counseling to promote smoking cessation for patients with cancer should involve assisting the patient to do the following: develop an awareness of the health risks related to continued smoking; devise and use alternative behaviors; implement the use of reinforcement strategies for cessation successes; and develop a sense of confidence and commitment about quitting as well as healthy lifestyle values. These strategies are discussed within the context of models and guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Ns denote number of studies in the analysis for Full Sample/Current Smokers at Cancer Diagnosis. Full Sample: 0-3 includes data from (4, 10, 34, 40, 42, 54, 63, 73, 80, 84, 110, 127, 132, 134, 135, 143, 145, 147, 154); 4-6 includes data from (51, 131, 153); 7-11 includes data from (49, 133); 12-59 includes data from (59, 79, 85, 86, 88, 91, 97, 100, 141, 152); 60+ includes data from (67, 70, 128); and Mixed includes data from (5, 29-31, 46, 52, 56, 62, 69, 90, 94, 95, 98, 103, 112, 115, 120-122, 125, 126, 130, 138). Current Smokers at Cancer Diagnosis: 0-3 includes data from (4, 34, 39, 40, 80, 82, 84, 110, 143, 149); 4-6 includes data from (76, 153); 7-11 includes data from (123); 12-59 includes data from (36, 97); 60+ includes data from (128); and Mixed includes data from (5, 35, 44, 46, 56, 112, 115, 125, 129, 138).…”
Section: Figurementioning
confidence: 99%
“…Ns denote number of studies in the analysis for Full Sample/Current Smokers at Cancer Diagnosis. Full Sample: 0-3 includes data from (4, 10, 34, 40, 42, 54, 63, 73, 80, 84, 110, 127, 132, 134, 135, 143, 145, 147, 154); 4-6 includes data from (51, 131, 153); 7-11 includes data from (49, 133); 12-59 includes data from (59, 79, 85, 86, 88, 91, 97, 100, 141, 152); 60+ includes data from (67, 70, 128); and Mixed includes data from (5, 29-31, 46, 52, 56, 62, 69, 90, 94, 95, 98, 103, 112, 115, 120-122, 125, 126, 130, 138). Current Smokers at Cancer Diagnosis: 0-3 includes data from (4, 34, 39, 40, 80, 82, 84, 110, 143, 149); 4-6 includes data from (76, 153); 7-11 includes data from (123); 12-59 includes data from (36, 97); 60+ includes data from (128); and Mixed includes data from (5, 35, 44, 46, 56, 112, 115, 125, 129, 138).…”
Section: Figurementioning
confidence: 99%
“…Two explanations may be offered. On the one hand, as reported by Irwin (2009) and Schnoll et al (2002), physical symptoms (e.g. fatigue) or emotional barriers (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Summarily, overcoming cancer-related barriers appears to play an important role in the formation of intention by enhancing the control individuals feel towards their disease (Schnoll et al, 2002). This suggests that among facets of the cancer experience that prevent this population from engaging in and adhering to therapeutic PA, cancer-related barriers are a key construct.…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled in a cessation program have a high prevalence of depressive symptoms, low self-confidence about quitting, low perceived risk of health problems, and low perceived benefits from smoking cessation; however, patients characterized by a shorter time since diagnosis, lower tobacco use and nicotine dependence, higher perceived risk of smoking, and higher perceived benefit of quitting were more motivated to quit (76). Other studies have shown that higher rates of smoking cessation were associated with higher levels of counter-conditioning and reinforcement management, lower levels of self-reevaluation, female sex, higher baseline health, lower nicotine dependence, surgical treatment (as opposed to radiotherapy), being non-Caucasian, and being in an “action” stage of change (71, 77, 78). However, lesser readiness to quit, higher nicotine dependence, higher cravings, lower education, younger age of initiation, higher level of pain, and smoking cessation less than 6 months prior to surgery have been associated with higher rates of relapse (75, 79, 80).…”
Section: Tobacco Cessation Treatmentmentioning
confidence: 99%